Perceived Changes in Teachers’ Professional Ethics and Students’ Moral Values: An Empirical Study Informed by Virtue Ethics and Moral Agency” - Malik, Sajad Ahmad; Ahangar, Imtiyaz Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This empirical study investigates the correlation between teachers’ professional ethics and students’ moral values in secondary schools, framed within virtue ethics and moral agency theoretical perspectives. Design/methodology/approach: Employing a quantitative descriptive-correlational design, data were collected from 300 secondary school teachers and 450 students using standardized scales. Statistical analyses included reliability testing, descriptive statistics, Pearson correlation, and linear regression. Findings: Results indicate moderate-to-low levels of professional ethics among teachers (M=3.12, SD=0.54) and moral values among students (M=2.95, SD=0.61). A significant positive correlation was found (r=.48, p<.01), with teacher ethics explaining 23% of variance in student moral values. Practical implications: Findings underscore the need for ethics-focused teacher development programs, integration of moral reflection in school culture, and policies supporting teacher autonomy. Originality/value: This study provides quantitative evidence linking teacher ethics to student moral development, integrating virtue ethics and moral agency in educational research.